COVID-19 vaccine capacity: Challenges and mitigation – The DCVMN perspective. Issue 35 (16th August 2021) - Hayman, Benoit; Suri, Rajinder; Prasad, Sai D.
Highlights: DCVMN members have strong interest in obtaining funding and technological support for COVID-19 vaccines. DCVMN members require technology transfers for modern technology platforms. More funding is required to support Phase III clinical trials in developing countries. Abstract: Vaccine manufacturers from developing countries have a proven track record of developing, producing, and supplying high-quality vaccines globally. However, due to the complexity of vaccine manufacturing, numerous stakeholder organizations support manufacturers across a variety of functions. To optimize the support from stakeholders it is instrumental to first understand which manufacturing processes these manufacturers require support for and what support functions are most beneficial. To this end, the Developing Countries Vaccine Manufacturers Network designed a comprehensive survey to assess the specific needs of the Network's member organizations. We found that almost all sampled manufacturers are interested in obtaining funding or technology transfers for COVID-19 vaccines. Furthermore, results indicated that manufacturers have a strong appetite for modern technology platforms, particularly RNA technologies. Scale-up, phase III clinical trials, and formulation were also key processes for which manufacturers require support.